Dual-task Interference Disrupts Parkinson's Gait Across Multiple Cognitive Domains. (21st May 2018) - Penko, Amanda L.; Streicher, Matthew C.; Koop, Mandy Miller; Dey, Tanujit; Rosenfeldt, Anson B.; Bazyk, Andrew S.; Alberts, Jay L.
Highlights: There was generalized worsening of gait with all cognitive tasks performed. Gait velocity decreased by the MCID under all dual-task conditions. Attention and problem solving tasks resulted in the greatest gait decrements. Gait decrements were observed bilaterally under dual-task constructs. Abstract: Gait dysfunction, a hallmark of Parkinson's disease, contributes to a relatively high incidence of falling. Gait function is further diminished during the performance of a motor-cognitive task (i.e., dual-task). It is unclear if Parkinson's disease-related dual-task deficits are related to a specific area of cognitive function or are the result of a more global decline in executive function. The aim of this project was to systematically evaluate gait performance to determine if gait dysfunction is restricted to certain types of executive function or a global phenomenon in individuals with Parkinson's disease. Twenty-three individuals with mild-moderate Parkinson's disease completed a series of dual-task conditions in which gait was paired with cognitive tasks requiring: working memory (0, 1, and 2-back), attention and problem solving (serial-7 subtraction), verbal memory (digit recall), semantic memory (Controlled Oral Word Association) and information processing speed (visual Stroop test). The results demonstrate that individuals with mild-moderate Parkinson's disease have a generalized worsening of spatial–temporal gait parameters regardless of the specific cognitive demand being performed concurrently. Overall, gait velocity decreased ( p  < 0.01) and stride and stance time both increased ( p  < 0.01) across all cognitive conditions. The attention and problem solving task resulted in the greatest number of gait parameter decrements. Results indicated that performance on cognitive tasks remained unchanged from single-task to dual-task conditions. Diminished gait performance under dual-task conditions across different cognitive function domains suggests a global Parkinson's disease-related deficit in information processing and regulation of gait.